Розробка системи електропостачання та електрозбереження хлібзаводу - Широцький, Володимир Сергійович; Shyrotskyi, Volodymyr (ЦНТУ, 2025)
В кваліфікаційній роботі виконано розробку системи електропостачання хлібзаводу згідно завдання. В роботі предоставлений огляд існуючих рішень, вибрано обладнання та принцип його роботи, розроблена система електропостачання та вибране необхідне обладнання. В спеціальному розділі розроблено заходи з енергозбереження в елементах системи електропостачання. In the qualification work, the development of the power supply system of the bread factory was carried out according to the task. The work provides an overview of existing solutions, equipment and the principle of its operation are selected, a power supply system is developed and the necessary equipment is selected. In a special section, energy saving measures are developed in the elements of the power supply system.
Development of a power supply and energy saving system for a bakery
Keywords: електропостачання; енергозбереження; електричні навантаження; режими роботи; power supply; energy saving; electrical loads; operating modes